Metabolic Positron Emission Tomography Response to Gamma Knife of the Ventral Intermediate Nucleus in Essential Tremor. Issue 6 (30th July 2018) - Verger, Antoine; Witjas, Tatiana; Carron, Romain; Eusebio, Alexandre; Boutin, Emmanuelle; Azulay, Jean-Philippe; Regis, Jean; Guedj, Eric
Abstract: BACKGROUND: To understand the substrates of response and nonresponse and to identify potential biomarkers for the selection and follow-up of patients with essential tremor (ET) treated with Gamma Knife (Elekta AB, Stockholm, Sweden) of the ventral intermediate nucleus (GKVIM). OBJECTIVE: To characterize positron emission tomography (PET) changes in the metabolism of glucose and metabolic connectivity in patients with ET treated by GKVIM through observational study. METHODS: Forty-two patients with right ET were referred to 18 F-fluorodesoxyglucose positron emission tomography ( 18 F-FDG PET) imaging before and after left GKVIM. Statistical Parametric Mapping T-score map comparisons were performed between pre- and post-GKVIM groups and between clinical responders and nonresponders. Metabolic connectivity was evaluated by the interregional correlation analysis method. RESULTS: After GKVIM, patients with ET exhibited decreased left thalamic metabolism, which was associated with remote metabolic decreases in the right cerebellum, left temporal gyri, and bilateral frontal gyri ( P < .05, family-wise error-corrected). Additionally, nonresponders (n = 7) showed metabolic decreases in the right temporo-occipital area ( P < .005 corrected for cluster volume) after GKVIM. The metabolism in this area was already reduced in nonresponders before treatment in comparison to that in responders and was predictive of future response (sensitivity: 89%; specificity: 71%). In nonresponder patients, strong connectivity between the left thalamus and right temporo-occipital area was found before GKVIM and was lost after treatment, whereas this connectivity remained weak and stable in responders. CONCLUSION: These findings could lead to better knowledge of the variability in the metabolic PET profiles among patients with ET, particularly the integration of 18 F-FDG PET imaging in the pretherapeutic evaluation of patients with refractory ET candidates for GKVIM.